Storage duration of vitrified embryos does not affect pregnancy and neonatal outcomes after frozen-thawed embryo transfer - Li, Xuelan; Guo, Pingping; Blockeel, Christophe; Li, Xinning; Deng, Ling; Yang, Jie; Li, Chujun; Lin, Min; Wu, Haocun; Cai, Guifeng; Hu, Yunzhao; Chen, Xin (Frontiers in Endocrinology, 2023)
Background: With the refinement of cryopreservation technology, the number of frozen-warmed embryo transfer (FET) cycles and cryopreserved embryos has increased rapidly. However, studies investigating the effect of storage duration on pregnancy outcomes after vitrification are limited and their results are controversial. Furthermore, the available studies did not take patients’ demographic nor clinical treatment characteristics into account and the cryo-storage duration was short. So this study aimed to explore the effect of storage duration of vitrified warmed embryos on pregnancy and neonatal outcomes in patients with good prognosis and long storage duration of vitrified embryos. Methods: This study was a bi-centre, retrospective study including 1037 women undergoing their first FET cycles following a fresh cycle from January 2012 until December 2021. Patients were divided into four storage groups in accordance with the storage duration of transferred embryos (612 patients in group I, with storage duration between 1 and 6 months; 202 patients in group II, with storage duration between 7 and 12 months; 141 patients in group III, with storage duration between 13 and 36 months; and 76 patients in group IV, with storage duration between 37 and 84 months). The pregnancy and neonatal outcomes were compared amongst different storage duration groups. Results: Amongst the different groups, no significant differences were observed in the pregnancy outcomes, including biochemical pregnancy rate, implantation rate, clinical pregnancy rate, ongoing pregnancy rate and live birth rate. In addition, no evidence of differences amongst different storage duration groups was observed in terms of preterm birth, birth length and low birthweight. Conclusions: The pregnancy and neonatal outcomes of embryos after vitrification were not impaired by storage duration up to 7 years.